Molecular Dynamics-Assisted Discovery of Novel Phosphodiesterase-5 Inhibitors Targeting a Unique Allosteric Pocket - Weihao Luo; Runduo Liu; Xinlin Cai; Qian Zhou; Chen Zhang (Molecules)
Phosphodiesterase-5 (PDE5) is a potent therapeutic target for the treatment of male erectile dysfunction and pulmonary arterial hypertension with several drugs available on the market. However, most of the reported PDE5 inhibitors lack specificity over PDE6, a holoenzyme in eleven PDE families, which may cause various adverse effects. Targeting a unique allosteric pocket has proved to be an effective approach to designing selective PDE5 inhibitors. In the present study, an integrated virtual screening procedure consisting of pharmacophore modeling screening, molecular docking, molecular dynamics simulations, and binding free energy calculations was applied to the discovery of novel PDE5 inhibitors targeting the allosteric pocket. Seven out of thirty-three molecules purchased from the SPECS database (a hitting accuracy of 21%) with novel scaffolds were PDE5 inhibitors with enzymatic inhibition ratios of more than 50% at a concentration of 10 μM. Predicted binding patterns indicate these hits fit well in the allosteric pocket in PDE5. In particular, compound AI-898/12177002 (IC50 = 1.6 μM) demonstrates over 10-fold selectivity towards PDE6, providing a novel scaffold for the optimization of potent and selective PDE5 inhibitors with less adverse effects.